Spin-correlated doublet pairs as intermediate states in charge separation processes. (2nd October 2017) - Kraffert, Felix; Behrends, Jan
ABSTRACT: Spin-correlated charge-carrier pairs play a crucial role as intermediate states in charge separation both in natural photosynthesis as well as in solar cells. Using transient electron paramagnetic resonance (trEPR) spectroscopy in combination with spectral simulations, we study spin-correlated polaron pairs in polymer:fullerene blends as organic solar cells materials. The semi-analytical simulations presented here are based on the well-established theoretical description of spin-correlated radical pairs in biological systems, however, explicitly considering the disordered nature of polymer:fullerene blends. The large degree of disorder leads to the fact that many different relative orientations between both polarons forming the spin-correlated pairs have to be taken into account. This has important implications for the spectra, which differ significantly from those of spin-correlated radical pairs with a fixed relative orientation. We systematically study the influence of exchange and dipolar couplings on the trEPR spectra and compare the simulation results to measured X- and Q-band trEPR spectra. Our results demonstrate that assuming dipolar couplings alone does not allow us to reproduce the experimental spectra. Due to the rather delocalised nature of polarons in conjugated organic semiconductors, a significant isotropic exchange coupling needs to be included to achieve good agreement between experiments and simulations. Abstract :